Analisis Implementasi Penanganan Pembiayaan Bermasalah (Kredit Macet) Pada UMKM Syariah Di Kecamatan Pasar Kemis - Fajri Chairul Umam; Maria Dewi Puspita (Shofanah Media Berkah, 2026)
This study aims to analyze the implementation of handling non-performing financing (bad loans) in Islamic Micro, Small, and Medium Enterprises (MSMEs) in the Pasar Kemis sub-district, Tangerang Regency. As one of the most densely populated industrial and residential areas, Pasar Kemis has great MSME potential but is also faced with a high risk of financing failure. The research method used is descriptive qualitative with a case study approach. Data collection was carried out through in-depth interviews with managers of Islamic microfinance institutions (BMT/KSPPS) and Islamic MSME actors in Pasar Kemis, as well as financial report documentation. The results showed that the factors causing non-performing financing consisted of internal factors (weakness of business management, mixing of personal and business finances, and misuse of funds) and external factors (decline in purchasing power of the community around the industrial area and fluctuations in raw material prices). The handling strategies implemented by Islamic financial institutions in Pasar Kemis include preventive measures (feasibility analysis using 5C + 1S principles) and curative measures through financing restructuring (rescheduling, reconditioning, and restructuring) aligned with sharia principles (Fatwa DSN-MUI No. 47/DSN-MUI/II/2005). This study recommends the importance of regular business assistance by financial institutions to minimize the risk of non-performing financing.